The Relationship Between The Habit Of Eating Traditional Processed Food Salting Techniques With The Incidence Of Hypertension At The Health Center Paringin, Balangan District, South Kalimantan - Amelia, Aisyaturridha (Jurnal Gizi dan Kesehatan Nusantara, 2023)
People's eating habits are dominated by food types derived from food sources through fermentation with the addition of kitchen salt. These salty foods cause a decline in the quality and function of blood vessels, heart, and other important organs, resulting in decreased immunity as well as increased oxidants, to metabolic disorders or diseases, and hypertension. This research was conducted to find out about the habit of consuming traditional food processing techniques with hypertension at Paringin Health Center. This research uses a quantitative method with a cross sectional approach. In this study there were 166 people. With 68 research samples. As well as data collection methods using interviews, observations and laboratory tests. The research found that the nutritional value of NaCl contained per 100 grams of processed foods such as fried rice pack has a NaCl content of 10.01 grams, iwak karate karate has a NaCl content of 9.40 grams, fried mandai has a NaCl content of 7.04 grams, fried wadi content of 6.42 grams, and fried wadi content of NaCl. It has a NaCl content of 5.23 grams.Keywords: Traditional Food Processing, Drying Techniques, Hypertension